Orthodontics-Surgery-Prosthodontics Teamwork - (:unkn) unknown (AVES, 2016)
The consciousness and expectations of orthodontic patients have evolved with the increasing esthetic requirements of the society. Therefore, interdisciplinary intervention is crucial to achieve better results. A 19-year-old female patient presenting with posterior cross-bite, anterior open-bite, and laterognathia applied for treatment with the chief complaint of her unpleasant general facial appearance. The treatment plan included surgically assisted rapid maxillary expansion (SARME), double jaw surgery, and prosthetic restoration of the anterior teeth. The corticotomy was performed under general anesthesia and was followed by SARME. After leveling, stainless steel wires were placed, and Class II elastics were used for the decompensation of incisor teeth inclination. During surgery, maxillary advancement and mandibular set back were performed. The laterognathia was corrected with the rotation of the maxilla and bone removal from the hypertrophic side of the mandibular corpus. Following the removal of the orthodontic appliances, home bleaching and prosthodontic rehabilitations were performed. The patient ended up with the ideal facial criteria and an esthetic smile after 18 months of treatment.
Keywords: Double jaw surgery; facial asymmetry; interdisciplinary treatment; FACIAL ASYMMETRY